Sensor-based scoring system for the fighting category in Pencak Silat - Nurul Ihsan; Yulkifli Yulkifli; Ahmaddul Hadi; Yohandri Yohandri; Deby Tri Mario; Novadri Ayubi; Aydin Karacam; Zsolt Németh; Bekir Erhan Orhan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The scoring system which still focuses on the jury's observations is one of the problems with Pencak Silat not being competed at the Olympics, so a technology-assisted solution is needed. This research aims to develop a scoring system based on sensor technology installed on body protectors for the fighting category in Pencak Silat. This research consists of tool design, feasibility testing, and implementation. The equipment components installed on the body protector include flex sensors, foam, an RFID reader, an Arduino, and NRF24L. A total of 9 experts were assigned to assess its feasibility, namely information and technology experts (n1=3), instruments experts (n2=3), and Pencak Silat experts (n3=3). Then, 120 male (n1=70; 18.67±3.28 years) and female (n2=50; 18.69±3.52 years) Pencak Silat athletes were involved in field trials. Data were analyzed using Aiken's V index, ICC, ANOVA, and independent samples t-test. The results showed that the average V index was 0.778; ANOVA and ICC also showed that there were no differences in assessments between experts (p>0.05) with very high reliability (p<0.05). Then, the independent sample t-test analysis results showed no significant differences between the two assessment systems (p>0.05). In conclusion, this tool can be used as an alternative scoring system for the fighting category in Pencak Silat, so it is hoped that it will be helpful to the jury and Pencak Silat practitioners in facilitating their performance in providing objective and transparent assessments.